Domestic hot water production system in a hospital: Energy audit and evaluation of measures to boost the solar contribution - Atienza Márquez, Antonio; Domínguez-Muñoz, Fernando; Fernández-Hernández, Francisco Ángel; Cejudo-López, José Manuel (Elsevier, 2022)
Hospitals consume large quantities of energy to produce hot water and offset the distribution and recirculation thermal losses. This paper analyses a solar thermal system combined with gas boilers for domestic hot water production in a medium-size hospital. The solar contribution to the total demand (27%) is below design expectations (75%), resulting in significant gas consumption. The energy audit conducted in the first part of the paper highlights the vast thermal loss through poorly insulated pipes as the primary cause of the poor solar fraction. This issue is endemic to hot water-intensive buildings. The second part of the paper addresses the techno-economic evaluation of energy retrofit measures to reach a solar fraction of 60%. The simulation results indicate that cost-optimised solutions generally expand the solar caption area by 43–57% and improve insulations to reduce thermal losses by 70%. Depending on carbon taxes, the cost of hot water production would be 31–41 cent-€/kWh, which represents a 15–45% reduction from the current costs. Under stringent climate policies, installing heat pumps may further enhance economic competitiveness. The indicators and charts developed in this work are helpful decision-making tools concerning the energy refurbishment of solar domestic hot water systems.
Keywords: Instalaciones solares de agua caliente; Hospital building; Domestic hot water (DHW); Solar thermal; Energy audit; Energy retrofit; Techno-economic analysis